Antimicrobial Activity Test of The Combination of Pineapple Leaf Extract (Ananas Comosus) and Green Betel Leaf Extract (Piper Betle L) Against Candida Albicans - Adjani Buaya; Yolanda Eliza Putri Lubis; Suandy Suandy (International Journal Labs, 2025)
Candida albicans is an opportunistic fungus that can cause infections, especially in individuals with low immune systems. Efforts to control this fungal infection can be done by utilizing natural ingredients as an alternative antifungal. Pineapple leaves (Ananas comosus) and green betel leaves (Piper betle L) are known to contain active compounds with antimicrobial properties. This study aims to determine the inhibitory power of a combination of pineapple leaf and green betel leaf extracts on the growth of Candida albicans and to compare their effectiveness at various concentrations. This research is a laboratory experimental study using the disc diffusion method. Three groups of extract concentration combinations were used: 20%, 40%, and 60%. The diameter of the inhibition zone was measured in millimeters, and data were analyzed using a one-way ANOVA test followed by a Tukey HSD test. The results showed that the 20% concentration produced the largest average inhibition zone diameter of 38.32 mm, while the 40% and 60% concentrations produced 28.46 mm and 28.31 mm, respectively. The ANOVA test showed a significant difference between groups (p < 0.05), and the Tukey HSD test showed that the 20% concentration was significantly different from the other two groups. The combination of pineapple leaf and green betel leaf extracts at a concentration of 20% was the most effective concentration in inhibiting the growth of Candida albicans compared to concentrations of 40% and 60%.